Crescimento, desenvolvimento e produtividade da camomila em diferentes datas de semeadura e espaçamento entre plantas - Silva, Jocélia Rosa da (2018)
Among the main factors that cause variation in the growth, development and productivity of chamomile and essential oil are the sowing date and plant spacing, but there is no consensus among researchers about the most appropriate spacing between plants, nor is there any indications regarding the date of sowing that aims at the maximum productive potential of chamomile for the climatic conditions of Santa Maria-RS. Thus, the main objectives of this work were to evaluate the growth, development and productivity of chapters and essential oil of chamomile in different sowing dates and spacing between plants, in addition to obtaining a model of leaf area for chamomile. An experiment was conducted in Santa Maria, RS, Brazil, with five sowing dates (03/18/2017, 04/28/2017, 06/30/2017, 07/28/2017 and 08/31/2017). Seven different spacing between plants were used, being 5, 10, 15, 20, 25, 30 and 40 cm. The variables used to obtain the leaf area model were leaf area (LA), leaf dry mass and specific leaf area (SLA) of chamomile. The growth variables were dry mass of leaves, reproductive structures and total aerial part of plants, as well as plant height, leaf area index and harvest index. The phenological variables reported were the accumulated thermal time for six subperiods in the interval between sowing and maturation, plastochron and final node number (FNN). The productive variables were the yield of dried floral chapters, yield and essential oil content. The spacing between plants, sowing date and phenological stage did not differ the SLA of the chamomile, being of 133 cm²g-1, as it did not differ, it was possible to obtain a single model for the LA estimation of chamomile. The model resulting from the LA data by the integrator presented optimum performance, being indicated for the determination of the LA of the chamomile when there is data of leaves dry mass. For the studied growth variables were no interaction between sowing date and plant spacing for the plants collected at different phenological stages, but both have an isolated effect on the growth of the chamomile. The sowing of March resulted in a greater growth of chamomile, and the sowing of August in smaller. In relation to the spacing between plants the spacing of 25 cm showed greater growth of the plants of chamomile. Regarding the phenological response, it should be noted that the spacing between plants did not influence the phenological development of the plants, but the date of sowing interfered with the thermal sum, plastochron and the final number of nodes. The dates of sowing affect the productivity of floral chapters, the content and productivity of chamomile essential oil.The highest values for these variables occur for the sowing performed on 18.03 and 28.04. There is a linear tendency to reduce the productivity of dry floral chapters of chamomile with increasing plant spacing in the row.